Effects of examination-induced stress on memory and blood pressure - Firoz Ahmed; Dinesh K. Dubey; Rinku Garg; Rani Srivastava (Journal of Family Medicine and Primary Care)
Stress has been defined in many ways as a state of psychological arousal that results when the external demand is beyond what one can cope with. Stress is caused by various factors called stressors. Medical students are subjected to different kinds of stressors, such as pressure of academics with obligation to succeed, an uncertain future and difficulties of integrating into the system and different teaching protocols, which may affect their learning ability and performance. Stress has a great impact on brain mainly in the form of impaired memory and on cardiovascular function in the form of increased heart rate and blood pressure. The study was planned to assess the effects of examination induced stress on memory and blood pressure. The study was longitudinal in nature conducted at Department of Physiology, Santosh Medical College, Ghaziabad, India. Initially 100 subjects were selected from 17-24 years of age group then all the subjects were divided into two groups of ‘slow-learners’ and ‘fast-learners’ based upon their past academic performances. Readings were taken at two stages of academic year, 05 months before pre-prof examination and 03 days before pre-prof examination. Blood Pressure were measured and the memory assessments were done by using 10 subtests of PGI memory scale. We found a significant increase in stress level 3 days before the examination, compared to 5 months before the examination which in turn affected both blood pressure and memory functions. But, slow-learners were affected more compared to fast-learners.